2013
DOI: 10.1177/1077558713496321
|View full text |Cite
|
Sign up to set email alerts
|

Complexity, Public Reporting, and Choice of Doctors

Abstract: Health care consumers often make choices that are imperfectly informed and inconsistent with their expressed preferences. Past research suggests that these shortcomings become more pronounced as choices become more complex, through either additional options or more performance metrics. But it is unclear why this is true: Consumer choice remains a "black box" that research has scarcely illuminated. In this article, we identify four pathways through which complexity may impair consumer choice. We examine these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…They presented PRWs featuring quality of care data in combination with written reviews. However, the combined format did not yield better physician selection results, especially if choices grew more complex with larger choice sets and more indicators and information present [55]. Hence, finding PRW formats in which health care consumers can voice their opinion on aspects that are deemed assessable, while condensing and summarizing technical quality of care information in a format that is understandable by health care consumers (as suggested by Hibbard et al [54]) should be the subject for further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They presented PRWs featuring quality of care data in combination with written reviews. However, the combined format did not yield better physician selection results, especially if choices grew more complex with larger choice sets and more indicators and information present [55]. Hence, finding PRW formats in which health care consumers can voice their opinion on aspects that are deemed assessable, while condensing and summarizing technical quality of care information in a format that is understandable by health care consumers (as suggested by Hibbard et al [54]) should be the subject for further research.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is alarming as lower educational levels have been associated with low health literacy [57], more difficulty in processing quality of care information, and less optimal health care choices [55,58,59]. These findings suggest that individuals who are most in need for tools that guide them toward a better search and assessment of Web-based information [60], attribute themselves higher expertise than they probably have from an objective point of view.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies suggest that maximizing the pertinence of publicly reported quality data for patients is likely to increase use of these data. 31,32 Narrative reviews are one mechanism for increasing both the pertinence and the ability to participate in assessing quality. Designing reporting systems that enable consumers to easily choose what data they view may increase utility and use of publicly reported quality data.…”
Section: Discussionmentioning
confidence: 99%
“…This requires additional research on how patient comments are appropriately "curated" to present experiences in ways that other consumers can most easily interpret (Greaves, Millett, and Nuki 2014). Reporting practices most also be designed to better assist consumers when they strive to integrate comments with quantitative metrics (Schlesinger et al 2014). For example, comments could be "tagged" with subject matter labels that match ratings from conventional surveys, tagged with a patient's health conditions so that users could learn from patients who match their treatment needs, or tagged with ratings that allow sorting based on negativepositive valence.…”
Section: Targeting Investments In Research Relevant To Patient-reportmentioning
confidence: 99%